Beneath the skin of conservation claims by the wildlife fashion industry: a rapid evidence assessment, brief survey, & novelty stress-test on objectivity of data used by key regulatory sectors concerning four example species - Warwick, Clifford; Steedman, Catrina; Arena, Phillip; Grant, Rachel (Frontiers in Conservation Science, 2026)
The wildlife fashion industry involves diverse products that include animal skin, feathers, fur, and curios as part of various apparel, footwear, and many other accessories. Positive messaging by advocates of the wildlife fashion industry frequently promotes products as sustainably sourced and beneficial for species conservation. To assess potential veracity of conservation claims by the wildlife fashion industry we conducted a rapid evidence assessment, brief survey, and novelty stress-test regarding data used by key regulatory sectors concerning four example species within the sector (Australian saltwater crocodiles (Crocodylus porosus), reticulated pythons (Malayopython reticulatus), Burmese pythons (Python bivittatus), and South African ostriches (Struthio camelus australis)). We collated information via online literature searches, requests to government agencies, and the CITES Secretariat. No relevant data were provided by any government agency nor by CITES to support claims that the wildlife fashion industry benefits conservation of the four target species. We conclude that reliance on the commercial sector for objective and impartial data or other input appears imprudent, and that both the nature and source of information used for policy-making requires transparency and reform. We recommend wider use of the precautionary principle, which should be supported with high-level monitoring and enforcement, as well as improved information and education.